Friction and mechanical properties of amino-treated graphene-filled epoxy composites: modification conditions and filler content. Issue 45 (16th July 2020) - Bao, Tianjiao; Wang, Zhiyong; Zhao, Yan; Wang, Yan; Yi, Xiaosu
Abstract : The enhancement in resistance to the propagation of cracks in epoxy composites by adding GO-0.5 results in excellent wear resistance. Abstract : It remains a challenge for graphene to reach its full potential as a lubricant and wear-resistant material in thermosetting resin composites. In this study, the mechanical properties and friction properties of amino-treated graphene-filled epoxy composites, which were influenced by the conditions for the modification of graphene and filler content, were investigated. The mechanical properties were measured by tensile examination and the tribological properties were determined using a ball-on-disk tribometer. The results showed that the composite filled with amino-treated graphene for a short reaction time exhibited the best tribological behavior, where the friction coefficient was 57.9% lower than that of the pure resin and the wear rate was 92.2% less than that of the neat resin. Simultaneously, this amino-treated graphene also resulted in enhanced mechanical properties and T g in the nanocomposite, implying its good crosslinking network and strong interface strength. The wear track analysis demonstrated that the excellent wear resistance was induced by its improved toughness, which restrained the crack propagation of fatigue wear and decreased the size of debris, promoting the formation of a transfer film, and thus protecting the contact surface. The tribological properties also varied with the concentration of the nanofiller, which showed the best performance at 0.2 wt%. Through the optimization of the modification conditions and concentration, this work highlights a promising strategy for the application of graphene-related materials in the field of tribology.